Characteristics and Context of Women Probationers and Parolees Who Engage in Violence. (March 2018) - Morash, Merry; Kashy, Deborah A.; Cobbina, Jennifer E.; Smith, Sandi W.
For a sample of 396 women on probation and parole, this article presents the results of qualitative analysis that shows the nature of violence for a subgroup of 75 women who were convicted of a violent act. For the full sample of 396, the article also presents results of quantitative analyses that identify correlates of violent behavior. Women's violent acts were most often assaults on people who were not intimate partners. Second and third most common violent acts were for assaults of an intimate partner and robbery, respectively. Quantitative analysis revealed that history of adult abuse and anger predicted violence. The effect of abuse on violent behavior was partially mediated by anger. Intercorrelations between anger, mental health problems, histories of being abused, and current substance abuse suggest the efficacy of assessing these attributes so that programming can provide individualized interventions that address co-occurring problems.